การเปิดรับข่าวสารและความต้องการเข้าร่วมกิจกรรมที่เกี่ยวข้องกับ วัฒนธรรมไทยสากลของชาวลาว - โชคเหรียญสุขชัย, กาญจนา (Journal of Business, Innovation and Sustainability (JBIS), 2016)
บทความนี้มีวัตถุประสงค์หลักเพื่อศึกษาพฤติกรรมการท่องเที่ยว การเปิดรับสื่อ การเปิดรับข่าวสารการท่องเที่ยว การค้นหาข่าวสารการท่องเที่ยวไทย การรับรู้วัฒนธรรมไทยสากล และระดับความต้องการเข้าร่วมกิจกรรมที่เกี่ยวข้องกับวัฒนธรรมไทยสากลโดยใช้การเก็บแบบสอบถามจำนวน 369 คน ในนครเวียงจันทร์ ผลการศึกษาพบว่า ชาวลาวส่วนใหญ่มีความถี่ในการท่องเที่ยวในและนอกประเทศแบบไม่แน่นอนแล้วแต่โอกาส ส่วนใหญ่เดินทางไปเอง ชอบท่องเที่ยวธรรมชาติ รู้จักสถานที่ท่องเที่ยวทั่วไปทางโทรทัศน์ หาข้อมูลการท่องเที่ยวทางสื่ออินเทอร์เน็ต รู้จักสถานที่ท่องเที่ยวไทยผ่านทางโทรทัศน์มากที่สุด วัฒนธรรมไทยสากลที่ชาวลาวรู้จัก 3 อันดับแรกคือ การปรุงอาหาร ศิลปะตกแต่ง และการถักทอ และกลุ่มตัวอย่างมีความต้องการท่องเที่ยวและเข้าร่วมทำกิจกรรมทางวัฒนธรรม 3 อันดับแรก คือ การเรียนหรือการฝึกเรื่องการอาชีพ การเรียนระยะสั้นในมหาวิทยาลัย และการรักษาด้วยการแพทย์แผนปัจจุบัน Information exposure and the need of activities which associated with the Thai Cultural Universals of the Laos The purposes of this article are: to examine travel behavior, the media and information exposure, information search on Thai Tourism, the perception on Thai cultural universals and the need of activities which associated with the Thai cultural universals of the Laos. The 369 questionnaires were collected in the city of Vientiane.The results showed that most of the Laos frequency travel in and outside country uncertainty and occasionally, had their own trips, liked natural attractions, had search travel information via the Internet and known tourist destinations in Thailand via television. Most Laos had known Thai Cooking, Decorative and Weaving. If they had a chance to visit Thailand, they would like to attend the short courses in universities, had the vocational training, and had the treatment with medicine. DOI: http://dx.doi.org/10.14456/becj.2016.12